2021
DOI: 10.1016/j.compbiomed.2021.104390
|View full text |Cite
|
Sign up to set email alerts
|

Exploring SARS-COV-2 structural proteins to design a multi-epitope vaccine using immunoinformatics approach: An in silico study

Abstract: In December 2019, a new virus called SARS-CoV-2 was reported in China and quickly spread to other parts of the world. The development of SARS-COV-2 vaccines has recently received much attention from numerous researchers. The present study aims to design an effective multi-epitope vaccine against SARS-COV-2 using the reverse vaccinology method. In this regard, structural proteins from SARS-COV-2, including the spike (S), envelope (E), membrane (M), and nucleocapsid (N) proteins, were selected as target antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 110 publications
0
21
0
Order By: Relevance
“…Yet we revealed a median variation rate of 18.6 variations per genome with an increasing rate of one more variation every 12.5 days, which is expectedly higher than what identified in earlier studies ( 36 , 37 ). Noteworthy, 27.8% of variations were identified in regions coding for structural proteins, this put more emphasis on the importance of monitoring SARS-CoV-2 variations especially in these regions, as these structural proteins are the main targets of the currently developed vaccines) ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet we revealed a median variation rate of 18.6 variations per genome with an increasing rate of one more variation every 12.5 days, which is expectedly higher than what identified in earlier studies ( 36 , 37 ). Noteworthy, 27.8% of variations were identified in regions coding for structural proteins, this put more emphasis on the importance of monitoring SARS-CoV-2 variations especially in these regions, as these structural proteins are the main targets of the currently developed vaccines) ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A different approach has been taken in several studies to search for potential vaccine candidates by targeting TLR4 to bind the epitope of the SARS-CoV2 spike protein [32], [34], [35]. Several studies on SARS-CoV2 have shown the importance of TLR4 in generating an effective immune response [36], [37].…”
Section: Covid-19mentioning
confidence: 99%
“…The antigen analysis, for example, helps to determine immunological epitopes that can trigger an immune response without causing the reversal of viral pathogenesis ( Dhama et al, 2020 , Mishra et al, 2020 ) In silico proteome analysis of the SARS-CoV-2 genome ( Mishra et al, 2020 , Wu et al, 2020 ) identified 29 encoded proteins ( Baruah et al, 2020 ). There are 14 open reading frames (ORFs): ORF1a, ORF1b, ORF 14, 9b, 8b, 7b, 7a, p6, 3a (papain-like protease), and 3b ( Baruah et al, 2020 , Sanami et al, 2021 ). ORF1a and ORF1b encode 16 different nonstructural proteins (NSPs) ( Baruah et al, 2020 , Tan et al, 2005 ).…”
Section: Severe Acute Respiratory Syndrome-coronavirus-2mentioning
confidence: 99%
“…ORF1a and ORF1b encode 16 different nonstructural proteins (NSPs) ( Baruah et al, 2020 , Tan et al, 2005 ). Other proteins that are encoded by the virus genome are the envelope protein (E), the membrane protein (M), spike glycoprotein S, and the nucleocapsid protein (N) ( Baruah et al, 2020 , Sanami et al, 2021 , Tan et al, 2005 ).…”
Section: Severe Acute Respiratory Syndrome-coronavirus-2mentioning
confidence: 99%
See 1 more Smart Citation